Fungsi Masjid sebagai Pusat Dakwah dalam Pemberdayaan Umat Muslim di Kecamatan Tanjung Senang Kota Bandar Lampung - Mulyadi Piliang; M. Bahri Ghazali; Jasmadi Jasmadi; M. Mawardi J. (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze the management and function of mosques as centers of civilization and empowerment of Muslims in Tanjung Seneng District, Bandar Lampung City. The study used a qualitative approach with a case study method. Data were obtained through observation, interviews with the Head of the Religious Affairs Office, village heads, mosque administrators, congregations, community leaders, and religious leaders, as well as documentation. All data were then analyzed using qualitative analysis techniques. The results of the study indicate that the success of mosque empowerment is highly dependent on the role of the mosque administrators in managing and developing religious activities. Da'wah activities in mosques are generally carried out thanks to the dedication, sincerity, and enthusiasm of the mosque administrators who voluntarily devote their time, energy, and thoughts to prospering the mosque while improving the religious quality of the congregation. The implementation of mosque functions is still dominated by worship activities, such as obligatory and sunnah prayers, regular religious studies, commemoration of Islamic holidays, management of zakat fitrah, and organizing the sacrifice. Organizational management is still carried out simply with planning that has not been systematically arranged. Social activities are also still limited to food sharing programs through Friday Blessings, distribution of takjil, and breaking the fast and sahur together during Ramadan. Furthermore, the development of Islamic outreach through the Youth of the Mosque (RISMA) has not been optimal due to limited management resources and a limited understanding of the organization's duties and functions.